TRATAMENTOS EFICIENTES DE POLUENTES ORGÂNICOS PERSISTENTES EM ÁGUA (RODAMINA B E ACETAMINOFENO) EMPREGANDO MnO₂ MODIFICADO COM Zn e Ti - FERNANDES, Rodolfo Araújo (2025)
The presence of so-called emerging pollutants in water bodies represents a growing environmental challenge due to their persistence and harmful effects on human health and aquatic ecosystems. Since conventional technologies have limitations in removing these compounds, semiconductors have been investigated as an advanced option for wastewater treatment. Although manganese-based compounds are attractive due to their low cost, easy availability, low toxicity, and good catalytic properties, they may require specific synthesis and application conditions, which motivates research into their optimization for industrial wastewater treatment. This study investigated the efficiency of MnO₂ and its congeners modified with Zn and Ti, MnO₂(I)-Zn and MnO₂(I)-Ti, for the treatment of synthetic wastewater containing Rhodamine B (RhB) and acetaminophen (ACT). The MnO₂-(Zn, Ti) oxides were synthesized by Mn²⁺ oxidation via permanganate and characterized using XRD, FTIR, RAMAN, and DRS. Characterization results confirmed the crystalline structure of α-MnO₂ and indicated a bandgap narrowing in the modified materials. The modified materials exhibited higher efficiency in the removal and degradation of the studied emerging pollutants, with MnO₂(I)-Zn achieving 97% RhB removal within 5 minutes and reaching equilibrium (97.5%) in 15 minutes. Additionally, up to 99% ACT removal was achieved in less than 1 minute under visible light irradiation. These findings suggest that MnO₂ modification with Zn and Ti enhances the catalytic capabilities of the materials, offering a promising and efficient solution for treating wastewater contaminated with dyes and pharmaceuticals.